Analisis Pengaruh Religiusitas dan Literasi Keuangan Syariah Terhadap Manajemen Keuangan Rumah Tangga: Studi di Sekolah Islam Terpadu Tunas Bangsa - Rudiyanto Rudiyanto; Zaid Fikri Haidar (Ikatan Da'i Indonesia, 2026)
Family financial management from the perspective of Islamic economics is influenced by religiosity and Islamic financial literacy, although the practice of usury is still common among housewives. This study analyses the effect of these two variables on household financial management among the academic community and parents of students at Tunas Bangsa Integrated Islamic School (SIT), Depok, using a descriptive quantitative design with purposive sampling (n=80 respondents). Data were collected via valid and reliable questionnaires (Cronbach's alpha=0.817) and analysed using multiple linear regression. The results show a positive simultaneous effect of religiosity (X1, β=0.053) and Islamic financial literacy (X2, β=0.528) on household financial management (Y), with R²=35.5%. Islamic financial literacy has a stronger partial effect. These findings emphasise the need to integrate Islamic financial literacy education into formal education to strengthen the economic resilience of Muslim households.